Chemical Toxicity of a Bipartite Mixture of Copper and Cadmium - Babukutty, Y.; Geetha, T.S.; Chacko, J. (Asian Journal of Chemistry, 2010)
Toxicity of a mixture containing varying ratios of copper and cadmium to a widely distributed estuarine clam Villorita cyprinodies var. cochinensis has been studied and the effects quantified using the models proposed by Marking and Dawson and by Koneman. Accumulation of copper over a period of 96 h has also been studied. An attempt has been made to explain the observed toxic effects on the basis of the Ligand Field Splitting Energies and Hard and Soft Acid and Base concept.